Pedigree genome data of an early-matured Geng/japonica glutinous rice mega variety Longgeng 57 - Lei, Yuanbao; Zhang, Yunjiang; Xu, Linyun; Ma, Wendong; Zhou, Ziqi; Li, Jie; Quan, Pengyu; Faruquee, Muhiuddin; Yang, Dechen; Zhang, Fan; Zhou, Yongli; Quan, Guangjun; et al. (Springer, 2024)
By using PacBio HiFi technology, we produced over 700 Gb of long-read sequencing (LRS) raw data; and by using Illumina paired-end whole-genome shotgun (WGS) sequencing technology, we generated more than 70 Gb of short-read sequencing (SRS) data. With LRS data, we assembled one genome and then generate a set of annotation data for an early-matured Geng/japonica glutinous rice mega variety genome, Longgeng 57 (LG57), which carries multiple elite traits including good grain quality and wide adaptability. Together with the SRS data from three parents of LG57, pedigree genome variations were called for three representative types of genes. These data sets can be used for deep variation mining, aid in the discovery of new insights into genome structure, function, and evolution, and help to provide essential support to biological research in general.